As contribuições da educação crítica para a emancipação do sujeito toxicômano - Pinto, Rômulo Fabriciano Gonzaga (2016)
This work is linked to the line of research "Cultural and Educational Processes". This is a survey based on the theoretical and methodological assumptions of Critical Theory of the Frankfurt School, from critical conception of non-formal education in the public health field. The research problem was developed by the question: How Body conceptions of, health and happiness are built socio-historically and what are their possible relationship with the formation of the subject drug addict The research technique used was the hermeneutic perspective with document analysis, from the theoretical framework. The general objective of this research was to understand the historical development of body categories, health and happiness, as well as other social mediations in the process of formation of the subject drug addict. Already the specific objectives were: to list, from the thought of Plato and Descartes, the elements for understanding the development of body categories, health and happiness; exhibit in dialogue with Foucault the history and development of health policies, their relationship with psychiatry and forms of care in the health field in the early modern era, reflect the Frankfurtian critical theory about the development of category instrumental reason and erudition human linked to the formation of the subject drug addict; understand Freud malaise in civilization, the specifics of the subject drug addict with psychoanalysis olivensteiniana prohibitionist drug policy, list the health care forms constituted as opposed to asylum-asylum policy in the twentieth century and XXI and the educational possibilities arising therefrom that may contribute to the emancipation of the subject drug addict by adorniana. A research critical theory originated from the therapeutic-pedagogical experience in mental health services in Goiânia, as well as the need to research, study and reflection of a field still little theoretical production. Therefore, we analyzed the documents that regulate the teaching process of Physical Education in CAPS-AD, aiming to present possible solutions to the construction of a critical education project in the public health service which can contribute to the emancipation of the subject drug addict. We conclude that, despite the limitations and contradictions, there is a possibility of therapeutic-critical pedagogical intervention in the field of public health which could help to the emancipation of the subject drug addict in the way of criticality.